Tertiary lymphoid structures in chronic rhinosinusitis with nasal polyps: spatial organization, pathological functions, and implications for surgical strategy and biologic therapy - Yu-Shan Lin; Guan-Jiang Huang; Biao-Qing Lu; Qi-Ping Luo; Zhi-Jun Fan; Xue-Sen Yang; Chao-Qing Long (Frontiers in Immunology, 2026)
Chronic rhinosinusitis with nasal polyps (CRSwNP) presents three persistent clinical enigmas that conventional immunological frameworks have failed to resolve. These include the paradox of locally elevated specific IgE in the absence of systemic sensitization, a high polyp recurrence rate exceeding 60% following technically complete functional endoscopic sinus surgery (FESS), and disease rebound observed in the majority of patients within 6 to 12 months after discontinuation of dupilumab. Converging lines of evidence suggest that tertiary lymphoid structures (TLS), organized ectopic lymphoid aggregates capable of sustaining autonomous adaptive immune responses, may represent a unifying structural framework that could contribute to all three phenomena. Within CRSwNP tissue, mature TLS are proposed to harbor functional germinal centers that drive local IgE class-switch recombination independent of systemic sensitization. These structures may also serve as protected niches for tissue-resident memory T (TRM) cells refractory to systemic biologic blockade, and they may maintain self-sustaining immune circuits that persist after surgical removal of gross polyp tissue. This review synthesizes current knowledge of TLS formation biology, proposes a Trifunctional TLS Model as a conceptual framework. It further integrates recent spatial transcriptomic data from large cohorts to hypothesize that TLS anatomical depth may determine functional phenotype and therapeutic vulnerability. We further propose a TLS grading framework as a research instrument to structure future validation studies, and outline hypothesis-driven, testable implications for surgical extent, biologic targeting strategies, and future research directions. If validated, reframing CRSwNP as a TLS-driven, structurally semi-autonomous inflammatory disease could shift the therapeutic paradigm from symptom suppression toward immunological restructuring.